Advanced Detection and Therapeutic Monitoring of Atherosclerotic Plaque Using CD36-Targeted Lipid Core Probe - Tingting Gao; Siqi Gao; Maolin Qiao; Chuanlong Lu; Heng Wang; Hongjiu Zhang; Lizheng Li; Shule Wang; Ruijing Zhang; Honglin Dong (Pharmaceutics)
Background: Atherosclerotic diseases, including coronary heart disease and cerebrovascular disease, are leading causes of morbidity and mortality worldwide. Atherosclerosis is a chronic vascular condition marked by the accumulation of lipid plaque within arterial walls. These plaques can become unstable and rupture, leading to thrombosis and subsequent cardiovascular events. Therefore, early identification of vulnerable plaque is critical for preventing such events. Objectives: This study aims to develop a novel imaging platform for atherosclerotic plaque by designing a molecular imaging probe based on fluorescent molecules that target lipid necrotic cores. The goal is to specifically detect high-risk plaque, enabling early diagnosis and intervention. Methods: Bioinformatic analysis and immunofluorescence were used to detect CD36 expression in human carotid plaque. CD36pep-ICG was synthesized using the Fmoc solid-phase peptide method. A series of experiments was conducted to characterize the probe’s properties. To assess imaging performance, probe concentration gradients were tested using FLI equipment. Ex vivo imaging was performed on atherosclerotic mice and treatment models to evaluate the probe’s targeting ability and effectiveness in monitoring disease progression. Results: The CD36 expression was significantly elevated in the core of plaque compared to distal regions. The CD36pep-ICG probe, specifically designed to target lipids, was successfully synthesized and exhibited excellent fluorescence properties. In animal models, FLI imaging demonstrated that the CD36pep-ICG probe selectively accumulated in atherosclerotic plaque, enabling precise plaque detection. Moreover, the probe was used to monitor the therapeutic efficacy of anti-atherosclerotic drugs. Conclusions: The CD36pep-ICG probe developed in this study is an effective molecular imaging tool for the specific identification of vulnerable atherosclerotic plaque, offering a novel approach for early diagnosis and treatment. Additionally, the probe shows promise in tracking the therapeutic effects of the drug, potentially advancing the precision treatment of cardiovascular diseases.